2022
DOI: 10.1002/inf2.12362
|View full text |Cite
|
Sign up to set email alerts
|

Design of superior electrostriction in BaTiO3‐based lead‐free relaxors via the formation of polarization nanoclusters

Abstract: Electrostrictive materials have wide applications in modern high-precision electronic devices. Driven by growing environmental concerns, there is demand for lead-free materials with superior electrostriction behaviors. In this study, we demonstrate a record-high electrostrictive coefficient of ~0.0712 m 4 C À2 in perovskite ferroelectric ceramics, along with hysteresis-free strain as well as excellent frequency and thermal stabilities, in lead-free BaTiO 3 -based ceramics through a polarization nanocluster des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Crystal structure based on long-range periodicity with randomly distributed species provides excellent convenience in describing crystalline solids' properties. Yet, emerging functional crystalline materials usually harbor locally correlated disorder that is deviated from the global long-range average structure, such as that with respect to the composition or atomic displacements [1][2][3][4] . Critically, such structural disorder has a profound impact on their functional properties.…”
mentioning
confidence: 99%
“…Crystal structure based on long-range periodicity with randomly distributed species provides excellent convenience in describing crystalline solids' properties. Yet, emerging functional crystalline materials usually harbor locally correlated disorder that is deviated from the global long-range average structure, such as that with respect to the composition or atomic displacements [1][2][3][4] . Critically, such structural disorder has a profound impact on their functional properties.…”
mentioning
confidence: 99%
“…The atomic-resolution displacement mapping gives the direct 2D distribution, but cannot provide the relation between local chemical and polar inhomogeneity. Interestingly, the atomic PDF based on total scattering is a tool that can offer quantitative information about local and subnanoscale structures. , The recent advances in big-box structure-refinement methodology enable to establish a 3D atomic configuration directly by fitting the experimental total scattering data. To construct the 3D nanoscale structure of BBT12, both neutron and X-ray total scattering data were collected. A big-box atomic configuration with 20 × 20 × 20 perovskite unit cells (40,000 atoms, approximately 80 × 80 × 80 Å 3 ) was refined according to a RMC algorithm by simultaneously fitting six experimental data, including neutron-based and X-ray-based reciprocal-space S ( Q ) data and real-space PDF G ( r ) data, and Bragg data.…”
Section: Resultsmentioning
confidence: 99%
“…We also point out that most theoretical and experimental studies of the static electro-and magnetostriction correspond to the thermodynamical equilibrium limit. Experimental studies of electrostriction have also revealed interesting phenomena, such as the giant electrostriction [15][16][17][18][19][20][21][22][23][24][25], negative electrostriction [26,27], and deformations of liquid crystals [28,29] and biological cells [30]. On the theoretical side, electrostriction has also been under extensive study [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%